2016
DOI: 10.18632/oncotarget.9155
|View full text |Cite
|
Sign up to set email alerts
|

Impact of suppression of tumorigenicity 14 (ST14)/serine protease 14 (Prss14) expression analysis on the prognosis and management of estrogen receptor negative breast cancer

Abstract: To elucidate the role of a type II transmembrane serine protease, ST14/Prss14, during breast cancer progression, we utilized publically accessible databases including TCGA, GEO, NCI-60, and CCLE. Survival of breast cancer patients with high ST14/Prss14 expression is significantly poor in estrogen receptor (ER) negative populations regardless of the ratios of ST14/Prss14 to its inhibitors, SPINT1 or SPINT2. In a clustering of 1085 selected EMT signature genes, ST14/Prss14 is located in the same cluster with CDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 76 publications
2
12
0
Order By: Relevance
“…To investigate the clinical relevance of this finding, a bioinformatics approach was utilized. Previously, we reported that high expression of epithin/PRSS14 in patients with ERnegative breast cancer indicated poor patient survival [12]. Consistently, we found that three out of four ER-negative patient samples showed higher expression of epithin/ PRSS14 in tumor than in normal tissues (Additional file 1: Figure S10).…”
Section: Eicd Induces Changes In Gene Expressionsupporting
confidence: 82%
See 1 more Smart Citation
“…To investigate the clinical relevance of this finding, a bioinformatics approach was utilized. Previously, we reported that high expression of epithin/PRSS14 in patients with ERnegative breast cancer indicated poor patient survival [12]. Consistently, we found that three out of four ER-negative patient samples showed higher expression of epithin/ PRSS14 in tumor than in normal tissues (Additional file 1: Figure S10).…”
Section: Eicd Induces Changes In Gene Expressionsupporting
confidence: 82%
“…Many studies have shown that epithin/PRSS14 is upregulated in a variety of human epithelial cancers [7] and is tightly linked to higher tumor grades and poorer survival of patients [8][9][10][11]. Recently, we reported from the analysis of public databases of patients with breast cancer that epithin/PRSS14 is a prominent prognosis marker for patients with estrogen receptor (ER)-negative breast cancer [12]. The role of epithin/ PRSS14 in metastasis and survival has been evaluated in multiple animal studies.…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier careful analysis of TCGA breast cancer patients, we showed that Prss14/epithin (ST14) is an excellent prognostic marker for highly metastatic ERbreast cancer (3). In this study, we have shown that expression profiles of PKCB (PKC and ST14 are in reasonably well-correlated (Fig.…”
Section: Implication Of Pkc and Jnk As Prognosis Markers As Well As supporting
confidence: 52%
“…Overexpression of Prss14/epithin is found in various epithelial cancer types (2). Particularly, ER-negative (ER -) breast cancer patients with poor prognosis express higher levels of Prss14/epithin (3). In our earlier report involving pathological examinations, we showed that prognosis of postsurgery esophageal cancer patients with higher Prss14/epithin expression is very poor (4).…”
mentioning
confidence: 92%
“…Serine protease 14 (PRSS14), also called epithin ( 14 ), matriptase ( 15 ), or membrane-type serine protease 1 ( 16 ), is a typical membrane-type serine protease that is overexpressed in multiple cancer cell lines and breast cancer tissues ( 17 18 ). Its role in breast cancer progression has been demonstrated in several conventional pathologic studies ( 19 20 21 ). When Prss14 hypomorphic mice, which express a minimal amount of Prss14, were crossed into spontaneous breast cancer transgenic mice, mouse mammary tumor virus (MMTV)-polyoma middle tumor-antigen (PyMT), tumor growth was significantly reduced ( 22 ).…”
Section: Introductionmentioning
confidence: 98%